Hypervascular Lesion in the Head of the Pancreas. Preoperative Angiography and Selective Embolization Results in Bloodless Operation - Ben-Ishay, Offir; Linder, Revital; Ofer, Amos; Kakiashvili, Eli; Kluger, Yoram (JOP. Journal of the Pancreas, 2012)
Context Pancreatic neuroendocrine tumors (PNETs) are rare tumors. These tumors are hypervascular in nature. Their surgical management is well described and practiced. Although hypervascular in their nature, preoperative angioembolization of the primary tumor is usually not indicated. Case report We describe a case of an extremely hypervascular PNET in the head of the pancreas that was managed with preoperative angioembolization that was followed by a Whipple operation that resulted in excellent recovery. Discussion Pre-operative angioembolization of pancreatic tumors, although previously reported, is exceedingly rare. The use of this technique prior to surgery is feasible and may result in bloodless surgery and better outcome. Image: Transarterial selective angiography of the celiac axis, showing a hypervascular lesion of the head of the pancreas.